STRATEGI GURU PAI DALAM PEMBELAJARAN MENULIS AL-QUR’AN MELALUI METODE DRILL SISWA DI SMPN 1 PULAU HANAUT KABUPATEN KOTAWARINGIN TIMUR - Rahmawati, Siti; Yufina, Auliya (ADDABANA: Jurnal Pendidikan Agama Islam, 2024)
Abstract: Realizing that many children can read the Koran but are less able to write the Koran. This is based on interviews with PAI teachers. So PAI teacher strategies are very important in the learning process so that children become enthusiastic about learning to write the Qur'an. This research discusses "PAI Teachers' Strategies in Learning to Write the Al-Qur'an Using the Drill Method for Class VII Students, Bapinang Hulu Village, Pulau Hanaut District, East Kotawaringin Regency, Central Kalimantan Province". The formulation of the problem in this research is: What are the strategies of PAI teachers in learning to write the Qur'an using the drill method for students at SMPN 1 Hanaut Island, East Kotawaringin Regency and what are the supporting and inhibiting aspects of PAI teachers in learning to write the Qur'an through the drill method? students at SMPN 1 Pulau Hanaut, East Kotawaringin Regency. The aim of this research is to describe PAI teachers' strategies in learning to write the Al-Qur'an through the drill method for students at SMPN 1 Hanaut Island, East Kotawaringin Regency and to describe what aspects support and hinder PAI teachers in learning to write the Al-Qur'an through this method. drill students at SMPN 1 Pulau Hanaut, East Kotawaringin Regency. The data subjects of this research are PAI teachers and class VII students of SMPN 1 Hanaut Island, East Kotawaringin Regency. Meanwhile, the object of this research is the strategy of Islamic Religious Education teachers in learning to write the Al-Qur'an through the drill method at SMPN 1 Pulau Hanaut, East Kotawaringin Regency. In extracting data the author used observation, interview and documentation techniques. Meanwhile, data processing techniques are data reduction, data presentation and data verification, then analyzed using qualitative analysis and then drawing conclusions inductively.Based on the results of this research, it was concluded that learning to write the Al-Qur'an through the drill method for class VII students at SMPN 1 Hanaut Island, East Kotawaringin Regency was going well. This can be seen from the drill method steps in learning to write the Al-Qur'an which are carried out in stages. This method is used to really help students learn to write the Al-Qur'an correctly, precisely and neatly. Meanwhile, the supporting and inhibiting aspects of PAI Teachers' Strategy in Learning to Write the Al-Qur'an Using the Drill Method for Students of SMPN 1 Hanaut Island, Kotawaringin Regency are: Supporting aspects are teachers who have an educational background in accordance with their field of education, have had quite a long teaching experience at the school. The infrastructure is sufficient because using this method does not require a lot of facilities. The inhibiting aspect is the student's talent and interest in participating in the learning process.  Keywords: Drill Method, Writing the Koran. Abstrak: Menyadari bahwa banyaknya anak yang bisa membaca Al-Qur’an tapi kurang mampu menulis Al-Qur’an. Hal ini berdasarkan wawancara dengan guru PAI. Sehingga strategi guru PAI sangat penting di dalam proses pembelajaran agar anak menjadi semangat dalam belajar menulis Al Qur’an. Penelitian ini membahas tentang “Starategi Guru PAI dalam Pembelajaran Menulis Al-Qur’an Melalui Metode Drill Siswa Kelas VII Kelurahan Bapinang Hulu Kecamatan Pulau Hanaut Kabupaten Kotawaringin Timur Provinsi Kalimatan Tengah”. Rumusan masalah pada penelitian ini adalah Bagaimana Strategi Guru PAI dalam pembelajaran menulis Al-Qur’an melalui metode drill siswa di SMPN 1 Pulau Hanaut Kabupaten Kotawaringin Timur dan Apa saja aspek pendukung dan penghambat guru PAI dalam pembelajaran menulis Al-Qur’an melalui metode drill siswa di SMPN 1 Pulau Hanaut Kabupaten Kotawaringin Timur. Tujuan penelitian ini adalah Mendeskripsikan strategi guru PAI dalam pembelajaran menulis Al-Qur’an melalui metode drill siswa di SMPN 1 Pulau Hanaut Kabupaten Kotawaringin Timur dan Mendeskripsikan apa saja aspek yang mendukung dan yang menghambat guru PAI dalam pembelajaran menulis Al-Qur’an melalui metode drill siswa di SMPN 1 Pulau Hanaut Kabupeten Kotawaringin Timur. Subjek data penelitian ini adalah guru PAI dan siswa kelas VII SMPN 1 Pulau Hanaut Kabupaten Kotawaringin Timur. Sedangkan objek penelitian ini adalah strategi guru Pendidikan Agama Islam dalam pembelajaran menulis Al-Qur’an melalui metode drill di SMPN 1 Pulau Hanaut Kabupaten Kotawaringin Timur. Dalam penggalian data penulis melakukan teknik observasi, wawancara dan dokumentasi. Sedangkan teknik pengolahan data adalah reduksi data, penyajian data dan verifikasi data, selanjutnya dianalisa dengan analisis kualitatif yang kemudian mengambil kesimpulan dengan cara induktif.Berdasarkan hasil penelitian ini memperoleh kesimpulan pembelajaran menulis Al-Qur’an melalui metode drill siswa kelas VII SMPN 1 Pulau Hanaut Kabupaten Kotawaringin Timur sudah berjalan dengan baik. hal ini terlihat dari  langkah-langkah metode drill dalam pembelajaran menulis Al-Qur’an yang dilakukan secara bertahap. Metode ini digunakan sangat membantu peserta didik dalam belajar menulis Al-Qur’an dengan benar, tepat dan rapi. Sementara Aspek pendukung dan penghambat Strategi Guru PAI Dalam Pembelajaran menulis Al-Qur’an Melalui Metode Drill Siswa SMPN 1 Pulau Hanaut Kabupaten Kotawaringin yaitu: Aspek pendukung adalah guru yang memiliki latar belakang pendidikan sesuai dengan bidang pendidikannya, pengalaman mengajar sudah cukup lama di sekolah tersebut. Sarana prasarana mencukupi karena penggunaan metode ini tidak banyak menggunakan sarana. Aspek Penghambat adalah bakat dan minat siswa dalam mengikuti proses pembelajaran.   Kata Kunci: Menulis A-lQur’an, Metode Drill.